PENGARUH PUPUK ORGANIK CAIR (POC) DENGAN MENGGUNAKAN BIOAKTIVATOR MOL TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN ANDEWI (Cichorium Endevi L.) - Dita aulia, Dewi; Nasrul, Muhammad; Setyawati, Harimbi (jurnal ATMOSPHERE, 2022)
Liquid organic fertilizer (POC) is a type of fertilizer that contains nutrients that are important in soil fertility and can be easily applied to soil for plant fertility. Utilization of POC can be used in the growth of Andewi (Cichorium Endevi L) which is an agrarian commodity that is in great demand. The purpose of this study was to determine how the effect of concentration, time of application, and soil type on the growth of Andewi (Cichorium Endevi L). Three factors are used in this experimental study. The first factor was the concentration of POC which was divided into five treatment levels, namely 10 mL, 15 mL, 20 mL, 25 mL and 30 mL. The second factor is the application of organic fertilizer which is divided into two levels, namely morning and evening. The third factor is the type of planting media with 2 levels, namely packaged planting media and soil in the pesantren area. Observational data were analyzed using analysis of variance (ANOVA). Analysis results from observations revealed that the concentration of organic fertilizer in liquid form, the time of application of liquid organic fertilizer and the type of planting media had an influence on the number of leaves, plant height and leaf width